The impact of ditch blocking on fluvial carbon export from a UK blanket bog. Issue 13 (20th June 2018) - Evans, Christopher D.; Peacock, Michael; Green, Sophie M.; Holden, Joseph; Chapman, Pippa J.; Lebron, Inma; Callaghan, Nathan; Grayson, Richard; Baird, Andrew J.
Abstract: We investigated the effects of ditch blocking on fluvial carbon concentrations and fluxes at a 5‐year, replicated, control‐intervention field experiment on a blanket peatland in North Wales, UK. The site was hydrologically instrumented, and run‐off via open and blocked ditches was analysed for dissolved organic carbon (DOC), particulate organic carbon, dissolved carbon dioxide, and dissolved methane. DOC was also analysed in peat porewater and overland flow. The hillslope experiment was embedded within a paired control‐intervention catchment study, with 3 years of preblocking and 6 years of postblocking data. Results from the hillslope showed large reductions in discharge via blocked ditches, with water partly redirected into hillslope surface and subsurface flows, and partly into remaining open ditches. We observed no impacts of ditch blocking on DOC, particulate organic carbon, dissolved carbon dioxide or methane in ditch waters, DOC in porewaters or overland flow, or stream water DOC at the paired catchment scale. Similar DOC concentrations in ditch water, overland flow, and porewater suggest that diverting flow from the ditch network to surface or subsurface flow had a limited impact on concentrations or fluxes of DOC entering the stream network. The subdued response of fluvial carbon to ditch blocking in our study may be attributable to the relatively low susceptibility of blanket peatlands to drainage, or to physical alterations of the peat since drainage. We conclude that ditch blocking cannot be always be expected to deliver reductions in fluvial carbon loss, or improvements in the quality of drinking water supplies.